Commodification of Culture in Marjan Syrup: Komodifikasi Budaya dalam Iklan Sirup Marjan - Novitasari, Fara Diva; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2023)
This study examines how Marjan raised the folklore culture of Lutung Kasarung and Purbasari in his advertisements. This study uses the theory of semiotic analysis of Roland Barthes and the commodification of Vincent Mosco. The purpose of this study was to determine the commodification of culture in Marjan syrup advertisements in the month of Ramadan, the version of Kutukan Lutung Kasarung and Purbasari by using Roland Barthes Semiotics Analysis of Marjan Syrup Advertisements. The research method used is qualitative. By using Roland Barthes Semiotics as an analytical knife of this research. The results showed that using Roland Barthes' semiotic analysis, it was found that there was a commodification of culture in the Marjan syrup advertisement. The actual use of the folklore culture of Lutung Kasarung and Purbasari has absolutely nothing to do with industry or products. However, it is used as an exchange rate whether in an economic concept or not. Marjan brought the folklore of Purbasari into his advertisement because what Purbasari felt was very suitable with the circumstances we face in fasting. From the initial feeling of joy, then getting a big obstacle to getting back with patience, just like when we run fasting, welcome with joy, run with many trials after successfully being able to feel the day of victory.